PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI SAMAKOI FARM, PURBALINGGA - Juli Handayani (Faculty of Social, Economics and Humanities, 2022)
This study aims to determine the effect of product quality on consumer purchasing decisions at Samakoi Farm, Purbalingga. The type of research is quantitative with a accidental sampling technique. Quantitative analysis technique with multiple linear regression analysis is used in this study. The dimensions of product quality in this study are product features, product durability, product reliability, conformance to specifications, product aesthetics. The results showed that from the five dimensions of product quality, there was one dimension of product durability that did not affect consumer purchasing decisions at Samakoi Farm, Purbalingga, while the other dimensions had an effect. However, if the test is carried out together there is an effect of product quality of 99.48% on consumer purchasing decisions at Samakoi Farm, Purbalingga. The high influence of these five dimensions shows the essence of a quality product.